2017
DOI: 10.1590/1518-8345.1511.2870
|View full text |Cite
|
Sign up to set email alerts
|

Needs of family caregivers in home care for older adults

Abstract: Objective:to reveal the felt and normative needs of primary family caregivers when providing instrumental support to older adults enrolled in a Home Care Program in a Primary Health Service in the South of Brazil. Methods:using Bradshaw's taxonomy of needs to explore the caregiver's felt needs (stated needs) and normative needs (defined by professionals), a mixed exploratory study was conducted in three steps: Descriptive quantitative phase with 39 older adults and their caregiver, using a data sheet based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 13 publications
1
42
0
10
Order By: Relevance
“…Regarding family caregivers, the present study, like other studies with this population, identified that the majority was women, with a mean age of 48.68 years and with a partner 17 - 19 . This reinforces the social role of women still present in society, which comes from a historically determined construction and interconnected with the fact that women did not perform activities outside the home, which gave them greater availability - and learning possibility - for the care of the home, children and family 18 .…”
Section: Discussionsupporting
confidence: 74%
“…Regarding family caregivers, the present study, like other studies with this population, identified that the majority was women, with a mean age of 48.68 years and with a partner 17 - 19 . This reinforces the social role of women still present in society, which comes from a historically determined construction and interconnected with the fact that women did not perform activities outside the home, which gave them greater availability - and learning possibility - for the care of the home, children and family 18 .…”
Section: Discussionsupporting
confidence: 74%
“…In addition, especially after stroke, older adults may need incontinence pads to manage their excreta, depending on the level of dependence. Incontinence diaper changes are complex as many caregivers are not accustomed to doing so routinely (20) . Incontinence diaper changes require training by health care professionals using a return demonstration method (20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…However, another national study with informal caregivers of the elderly identified that they often experience doubts about these activities. Patient transfers are usually learned during daily care, without guidance from health professionals (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These adults require assistance for daily activities and they are cared for by their own family at home [3]. The family caregivers face difficulties related to the instrumental, emotional and financial support and also the lack of knowledge and skills to perform the activities of care [4]. Support programs for caregivers after hospital discharge have demonstrated beneficial effects when structured in training interventions for family caregivers so that stroke survivors can receive proper care at home [5, 6].…”
Section: Introductionmentioning
confidence: 99%